Development of critical K dilution curves for diagnosing sweetpotato K status - He, Weichen; Li, Jing; Lu, Yanjun; Chen, Shaojie; Deng, Lijuan; Xu, Ximing; Zhu, Yueming; Jin, Minghuan; Liu, Yuheng; Lu, Guoquan; Lv, Zunfu (Frontiers in Plant Science, 2023)
Scientific and reasonable application of potassium fertilizer is an important agronomic measure to achieve high yield and high quality of sweetpotato, and it is of great significance to determine the appropriate amount of potassium fertilizer in the field. For this we constructing a model of the critical K dilution curve (CKDC) of sweetpotato under different N levels to determine crop nutritional statuses. In this study, a 3-year field experiment was conducted in Zhejiang Province in China, using two nitrogen levels (N0: 0 kg ha−1 and N1: 120 kg ha−1) and five K fertilization rates (K0: 0, K1: 75, K2: 150, K3: 225, K4: 300 kg ha−1) for two sweetpotato cultivars of ‘Shang 19’ and ‘Yan 25’. Plant dry matter first increased and then decreased and the K concentration increased continuously with an increase in K application rate. The required amount of K fertilizer to achieve maximum sweetpotato yield under high N conditions was greater than that under low nitrogen conditions. A new CKDC based on dry matter and K concentration was created to assess K nutrition in sweetpotato. At two N levels, CKDC was expressed by the negative power function equation, aboveground: Kc(N0)=5.30W-0.463, R2=0.79, and Kc(N1)=4.23W-0.298, R2=0.78, under-ground: Kc(N0)=1.38W-0.125, R2=0.81, and Kc(N1)=1.32W-0.132, R2=0.72；whole-plant: Kc(N0)=4.31W-0.421, R2=0.80; Kc(N1)=3.89W-0.415, R2=0.79. There is no significantly different for CKDC of whole-plant and underground between N0 and N1 levels, while there is significantly different for CKDC of aboveground between N0 and N1 levels. N fertilizer can strengthen the dilution effect of K concentration, and its effect on the aboveground is greater than that on the underground and whole-plant. Then, potassium nutrition indexes were constructed to identify K nutrition status and could be used as a reliable indicator for K nutrition diagnosis of sweetpotato. The results provide a theoretical basis to improve K fertilization management and sustainability of sweetpotato.